Molecular characterisation of selective proteins from plant photosystem II - Heller, Jiří (Jihočeská univerzita, 2013)
This qualification work is trying to shed a little bit more light on some proteins present in higher plants, which structure and function in photosynthetic reaction remain unclear. In particular it treats proteins of photosystem II, called PsbR, PsbW and PsbX that are responsible for photosynthetic reaction optimization. This thesis contains data about proteins acquisition and their sequences elucidation.
Molecular characterisation of selective proteins from plant photosystem II
Keywords: photosystem II; PsbR; proteins; nucleotide sequence; PsbW; PsbX; photosystem II; PsbR; proteins; nucleotide sequence; PsbW; PsbX